Estudio del veneno de serpientes: tipos y tratamientos - Rojo Solís, C.; Pérez Nogués, M.; Vicente Ruiz, Mª L. De; Encinas Cerezo, Mª T. (Revista Complutense de Ciencias Veterinarias, 2008)
Snake venoms are mixtures of more than 20 different polypeptides where enzymes, toxins and small peptides are included. Snakes inoculate their venom during the bite and then different envenomations can occur. The symptoms are described by two pathological processes: neurotoxic and haemotoxic. The gravity of the intoxication depends on some venom, bite and catch factors and sometimes the injuries can be everlasting. When a human being is bitten by a venomous snake, three steps must be taken: first aid (venom extraction and lymphatic circulation cut) and etiological (specific anti-venom serum administration) and symptomatic (pharmacological or surgical) treatment.